KHARAKTERISASI ENZIM KASAR GLUKOAMILASE DARI Saccharomycopsis sp. - Elidar Naiola (Research Center for Biology-Indonesian Institute of Sciences, 2006)
Saccharomycopsis sp. produced glucoamylase (a-1,4 glucanglucohydrolase; EC 3.2.1.3) shown by the presence of clear zone on media containing 0.2% yeast extract, 0.5% pepton, 0.3% KH2PO4, 0.05% MgSO4. 7H2O, 0.01% CaClr2H2O, 2% agar and 2% soluble starch. In liquid media containing soluble starch glucoamylase production reached a maximum at 2 days fermentation, with levels of 4.2 x 10 U/ml (one unit activity is define as micromoles of glucose produce per ml per minute).Studies on the glucoamylase characterization revealed that the optimum temperature for activity was 40°C - 50°C. The enzyme was stable for lh at 45